Using best-worst scaling method to examine consumers’ value preferences: A multidimensional perspective - Shehely Parvin (Taylor & Francis Group, 2016)
Unlike most prior studies, this study reconceptualizes the perceived value construct from the multidimensional perspective by incorporating the aesthetic and altruistic values from Holbrook’s value typology with the Theory of Consumption Value. Moreover, this study is a pioneer in measuring the construct of multidimensional perceived value with the Best-Worst Scaling method instead of rating scales to fill methodological deficiency in the literature. This study collected data through web-based survey using online consumer panels. Hierarchical cluster analysis used as the major data analysis technique. Results indicate consumers can be segmented on the basis of their preferences. Therefore, the use of the cluster analysis of the value dimensions would permit practitioners to develop more effective market segmentation strategies in order to attain sustainable competitive advantage in the growing hospitality and tourism industry.